A rare presentation of severe alloimmune hemolytic disease of newborn pertaining to minor blood group ‘c’ incompatibility: a case report and review of literature - Shah, Kruti; Bhatt, Shwetal; Chanpura, Vaishali (International Journal of Contemporary Pediatrics, 2024)
Hyperbilirubinemia is one of the most widely seen causes of neonatal morbidity. Haemolytic disease of fetus and newborn is caused by maternal alloantibodies to the fetal RBCs. It is responsible for incompatibility between maternal and fetal blood groups, which results in destruction of fetal red blood cells causing hyperbilirubinemia. ABO and Rh incompatibility are the most common causes of severe indirect hyperbilirubinemia. Besides ABO and Rh isoimmunization, minor blood group incompatibilities such as anti-Kell, anti-C, anti-c, anti-E, anti MNS, Duffy, KIDD, P, Lutheran and Lewis have also been identified as causes of severe neonatal jaundice with an incidence of 385/1,00,000 live births in South-East Asia. We, hereby report a rare case of a full term 2.2 kg newborn presented with severe anemia with reticulocytosis and neonatal hyperbilirubinemia at second hour of life. In view of strongly positive DCT and no Rh negative or ABO setting, minor blood group incompatibility screening test was performed in the mother which revealed presence of multiple alloantibodies; however, the red cell phenotyping confirmed the presence of anti-c antibodies in maternal sera responsible for neonatal alloimmune haemolytic anemia. The baby was offered intensive phototherapy with intravenous immunoglobulin.